High-Stakes Testing in the Warm Heart of Africa:The Challenges and Successes of the Malawi National Examinations Board - Chakwera, Elias; Khembo, Dafter; Sireci, Stephen G. (Education Policy Analysis Archives, 2004)
In the United States, tests are held to high standards of quality. In developing countries such as Malawi, psychometricians must deal with these same high standards as well as several additional pressures such as widespread cheating, test administration difficulties due to challenging landscapes and poor resources, difficulties in reliably scoring performance assessments, and extreme scrutiny from political parties and the popular press. The purposes of this paper are to (a) familiarize the measurement community in the US about Malawi’sassessment programs, (b) discuss some of the unique challenges inherent in such a program, (c) compare testing conditions and test administration formats between Malawi and the US, and (d) provide suggestions for improving large-scale testing in countries such as the US and Malawi. By learning how a small country instituted and supports its current testing programs, a broader perspective on resolving current measurement problems throughout the world will emerge.